Peningkatan Keterampilan Merancang Konten Pembelajaran dan Evaluasi Formatif Menggunakan Pendekatan Permainan - Sukirman Sukirman; Dias Aziz Pramudita; Muhammad Rizky Aminudin; Abdylla Adhiyasa Nugroho (Warta LPM, 2023)
Designing learning content and its evaluation is very necessary in teaching and learning activities to determine the extent to which results have achieved and its effectiveness. However, the evaluationa are sometimes still use traditional methods which might actually make students worry about the final result. In fact, this concern should be avoided in order to obtain maximum results. One strategy is to use a game approach, an evaluation model to measure abilities by utilizing games. The purpose of this activity is to improve partners' ability to design learning content and its evaluation, especially formative evaluation, using a game settings. The tools used for evaluation is Kahoot!, a web-based and mobile game platform that can be filled in online questions. The partners involved in this activity were teachers from various subjects of SMK Muhammadiyah 1 Klaten Tengah (6 people), SMK Muhammadiyah 3 Klaten tengah (9 people), and SMK Muhammadiyah 4 Klaten Tengah (6 people) for a total of 21. The method applied in this activity consists of 4 stages, start from analysis, formulation, solutive action, and evaluation. Solutive action is realized in the form of a workshop which is divided into two sessions, namely a theoretical session and a practical session. Based on the evaluation carried out between before and after the activity, it was found that the participants knew better how to design learning content in the form of videos using existing software. In addition, participants also know how to create formative evaluation tools using a game approach with the Kahoot! platform. Thus it can be concluded that the knowledge and skills of the participants became better after the activity.